Performance Evaluation and Army Recruiting - Dertouzos, James N. (RAND Corporation, 2008)
Traditional performance metrics, such as number of contracts signed per month per Army recruiter, do not adequately measure recruiter effort, skill, and productivity. The authors develop a "preferred performance metric" that takes into account the difficulty of recruiting different types of youth in various markets and propose short-term changes to the system that would more accurately assess recruiter effort and skill.